Validation of a modified version of the adult developmental eye movement test - Andrés Gené-Sampedro (Nature Portfolio, 2021)
Abstract This study evaluates in terms of reliability, internal consistency, and validity a modification of the Adult Developmental Eye Movement (ADEM) test, ADEM with distractors (ADEMd), designed to analyse oculomotor system, visual processing and visual attentional behaviour. 302 healthy subjects participated in the study (20–86 years old). Intrasession repeatability was evaluated by analysing the correlation between the time needed to read different parts of the test. Inter-session analyses were carried in 40 subjects by calculating intraclass correlation coefficients and using the Bland–Altman method. Validity was assessed in the outcomes obtained according to age as well as investigating the correlation between ADEMd and attentional useful field of vision (UFOV) test. Correlation coefficients between times need to read each sheet were ≥ 0.95 (p < 0.001). The inter-session intraclass correlation coefficient ranged from 0.81 in the horizontal distractor sheet to 0.97 in the vertical sheet. Bland–Altman analysis showed clinically acceptable limits of agreement. Statistically significant correlations were found between age and ADEMd outcomes (r ≥ 0.55, p < 0.001). Processing velocity, divided attention and selective attention measured with the UFOV were correlated with the horizontal distractor times (r ≥ 0.32, p < 0.001). ADEMd test may be a useful clinical tool to evaluate the combined interaction of ocular movements and visual attentional behaviour.